Hybrid stent in management of malignant airway obstruction with carina esophageal fistula: A case report. Issue 14 (7th April 2023) - Zhu, Chenghua; Liu, Jingning; Ke, Mingyao; Yong, Yazhi; Luo, Bingqing; Feng, Ganzhu
Abstract : Rationale: Airway stents have been developed rapidly to treat airway stenosis and fistula caused by various reasons. Malignant conditions that lead to central airway obstruction, especially the invasion of trachea carina and formation of esophageal fistula, are still a challenge for clinicians. Patient concerns: A 61-year-old man presented with malignant airway obstruction and fistula between trachea carina and esophagus accompanied by severe respiratory failure. Diagnosis: The patient was clinically diagnosed with esophageal squamous cell cancer of stage IV, carina esophageal fistula, severe pneumonia, hypoproteinemia. Interventions: Y-shaped covered metallic stent and Y-type silicone stent (hybrid stent) were placed in the airway to increase tracheal patency, block the fistula and perform carinal plasty. Outcomes: The clinical symptoms of the patient improved rapidly and the lung infection was controlled effectively. This patient was followed up for more than 2 month, and the quality of life was better than before. Lessons: Hybrid stent can be used as 1 of options for airway reconstruction and palliative treatment for patients with complex airway diseases caused by malignant tumors.